Hubungan Antara Pengajaran Bahasa Inggris Dan Pengajaran Sastera Inggris - HALIMAH TUSSA'DIAH (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
In the teaching of language especially English, the lecturer can apply various materials and teaching methods/strategies; one of them is by using English literature . The use of Engglish literature can be said as an active method. It is said so because it enables considerable practice. The lecturer must naturally innitiate and direct this practice since it cannot possibly originate spontaniously. Literary work contains superiorities which cannot be found in other kinds of instruments, and which only can be conveyed through the use of language, in the teaching of language, literature can be the source of various examples of the language aspects since literature is provided with abundancy material. Both language and literary are related each other.